ANALISIS PERBANDINGAN KINERJA KEUANGAN SEBELUM DAN SESUDAH PENERAPAN PSAK 72 PADA PERUSAHAAN INFRASTRUKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Nandini Ayu Mazaya (2022)
The purpose of this study is to see the differences of financial performance before and after the application of PSAK 72. Financial performance uses liquidity ratios, solvency ratios and profitability ratios. The liquidity ratio is proxied by the current ratio, then the solvency ratio is proxied by the debt to asset ratio, and the profitability ratio is proxied by the net profit margin. Each of these financial performance variables is compared before and after the company implements PSAK 72. The object in this study is the infrastructure company listed in the IDX- Industrial Classification. The sample was selected using a purposive sampling technique so that the sample obtained was 67 samples. The software or tool used to test the hypothesis is SPSS version 26. The results of this study indicate that 1) there is no difference in the current ratio between before and after the application of PSAK 72; 2) There is no difference in the debt asset to ratio between before and after the application of PSAK 72; 3) There is a significant negative difference in net profit margin between before and after the implementation of PSAK 72.